Soil nitrogen availability under grasses of different palatability in a temperate semi-arid rangeland of central Argentina - Moretto, Alicia Susana (2002)
Grazing by domestic livestock is frequently associated with the replacement of high-nutrient palatable species with low-nutrient unpalatable species, which may have a substantial effect on nutrient cycling. The objective of the present study was to compare soil N availability and net N mineralization in soils under Poa ligularis (palatable grass) with those in soils under Stipa tenuissima (unpalatable grass) in a temperate semi-arid rangeland of central Argentina. Nitrogen availability and net mineralization under laboratory and field conditions were measured. Soil N availability under P. ligularis was higher than or similar to soil N availability under S. tenuissima. In situ net N mineralization in the soil under P. ligularis was lower than or similar to net N mineralization in the soil under S. tenuissima. Potential net N mineralization was greater in the soil under P. ligularis than in the soil under S. tenuissima. Our results suggest that the replacement of palatable grasses by unpalatable grasses in the temperate semi-arid rangelands of central Argentina may imply a reduction in the rate of nutrient cycling.